Expeditious Fabrication Characterization of Metal Interdigitated Transducer on Polyimide film for Biosensing Application - Subramani, I.G. (Institute of Electrical and Electronics Engineers Inc., 2019)
Interdigitated electrode (IDE) as transducer in biosensor usually fabricated through tedious, time consuming photolithography technique by using rigid substrate such as silicon and glass. The material type and geometry of the IDE is one of the important factor for an enhanced sensitivity of the device. Flexible substrate, polyimide have been employed as alternatives to fabricate more sensitive, cheaper and robust small devices. In this paper, silver (Ag) and copper (Cu) IDEs was fabricated on polyimide substrate via one step radio frequency sputtering technique by transferring the pattern of IDE from Perspex hard mask onto polyimide substrate. Design of the IDE was drawn using AutoCAD 2018 software with appropriate geometry and Perspex hard mask was cut through laser cutting technique. IDE with two different surface area, circle shaped and square shaped was fabricated for each material type (silver and copper). High power microscope (HPM) was used to verify the dimensions of the fabricated IDE and to investigate optimum sputtering time. Voltage analysis demonstrate that Ag based circular shaped IDE with 0.8 mm gap dimension resulted 1.15 Ã 10-2 V, greater electrical behavior compares to copper based IDE. Â© 2019 IEEE.